A comparison of successful versus failed nonoperative treatment approaches in patients with degenerative conditions of the lumbar spine. (April 2021) - Davison, Mark A.; Lilly, Daniel T.; Moreno, Jessica; Bagley, Carlos; Adogwa, Owoicho
Highlights: A total of 531, 980 patients with lumbar stenosis or spondylolisthesis were studied. The majority of lumbar spine patients were successfully managed nonoperatively. Smoking, obesity, and opioid use were associated with nonoperative therapy failure. Patients failing nonoperative therapy spent double vs those successfully treated. Abstract: Identifying an optimal composition of nonoperative therapies to trial in patients suffering from degenerative lumbar spine conditions prior to surgical management remains challenging. Contrasting successful versus failed nonoperative treatment approaches may provide clinicians with valuable insight. The purpose of this study was to compare the nonoperative therapy regimens in degenerative lumbar spine disorder patients successfully managed conservatively versus patients who failed primary treatment and opted for lumbar fusion surgery. Clinical records from patients diagnosed with lumbar stenosis or spondylolisthesis from 2007 to 2017 were gathered from a comprehensive insurance database. Patients were separated into two cohorts: patients managed successfully with nonoperative therapies and patients who failed conservative therapy and underwent lumbar fusion surgery. Nonoperative therapy utilization by the two cohorts were collected across a 2-year surveillance window. A total of 531, 980 adult patients with lumbar stenosis or spondylolisthesis comprised the base population. There were 523, 031 patients (98.3%) successfully treated with conservative management alone, while 8, 949 patients (1.7%) ultimately failed nonoperative management and opted for lumbar fusion. Conservative therapy failure rates were especially high in patients with a smoking history (2.1%) and those utilizing lumbar epidural steroid injections (LESIs) (3.7%). A greater percentage of patients who failed conservative management utilized opioid medications (p < 0.0001), muscle relaxants (p < 0.0001), and LESIs (p < 0.0001). Patients who failed nonoperative management spent more than double than the successfully treated cohort (failed cohort: $1806.49 per patient; successful cohort: $768.50 per patient). In a multivariate logistic regression model, smoking, obesity and prolonged opioid use were independently associated with failure of nonoperative treatment.